STRATEGI HUMAS PONDOK PESANTREN AR-RAUDLATUL HASANAH DALAM MENINGKATKAN CITRA POSITIF PADA MASYARAKAT SUMATERA UTARA - Nuraina Nabilah; Nurhanifah (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) AMIK Indonesia, 2023)
The purpose of this study was to examine the extent to which Public Relations played an important role in improving the image of the Ar-Raudlatul Hasanah Islamic Boarding School among the public. This study also aims to analyze the strategy implemented by the Public Relations of the Islamic boarding school Ar-Raudlatul Hasanah to reinforce the positive image of the perpetrators in the community. The approach used in this study is a qualitative descriptive one, with data obtained through interviews, observations and literature reviews. The data analysis process includes data collection, data reduction, and drawing conclusions. The results of this study confirm that the Public Relations role of the Ar-Raudlatul Hasanah Islamic Boarding School is of particular importance in improving and maintaining a positive image of the Poidsren in the community. In fact, the role of Public Relations is now an essential and irreplaceable element in the context of Islamic boarding schools. The Public Relations efforts of the Ar-Raudlatul Hasanah Islamic Boarding School to enhance the image of the Islamic boarding school are carried out by increasing communication with the community outside the Islamic boarding school, establishing have good relations with other Muslim boarding schools and use social media as a means to widely spread information about the Ar-Raudlatul Hasanah Islamic Boarding School. In addition, the Public Relations Department of the Ar-Raudlatul Hasanah Islamic Boarding School also reviews each activity planned and carried out, as part of its ongoing efforts to improve the School's performance and image Islamic boarding.